Boundary Layer Flow Due To A Moving Flat Plate In Micropolar Fluid - Salleh, Mohd. Zuki; Mohd. Rohni, Azizah; Amin, Norsarahaida (Penerbit UTM Press, 2005)
The mathematical model for a boundary layer flow due to a moving flat plate in micropolar fluid is discussed. The plate is moving continuously in the positive x-direction with a constant velocity. The governing boundary-layer equations are solved numerically using an implicit finite-difference scheme. Numerical results presented include the reduced velocity profiles, gyration component profiles and the development of wall shear stress. The results obtained, when the material parameter K = 0 (Newtonian fluid) showed excellent agreement with those for viscous fluids. Further, the wall shear stress increases with increasing K. For fixed K, the wall shear, stress decreases and the gyration component increases with increasing values of n, in the range 0>n>1 where n is a ratio of the gyration vector component and the fluid shear stress at the wall.